2017
DOI: 10.1016/j.jns.2016.12.028
|View full text |Cite
|
Sign up to set email alerts
|

The test accuracy of the Montreal Cognitive Assessment (MoCA) by stroke lateralisation

Abstract: Background: The Montreal Cognitive Assessment (MoCA) is an increasingly popular screening tool for detecting cognitive impairment post-stroke. However its' test accuracy by stroke lateralisation is as yet unknown. Aim: Our aim was to investigate whether the test accuracy of the MoCA differs by stroke lateralisation across different cognitive domains. Methods: We retrospectively examined the cognitive profiles of 228 subacute stroke patients (86 Left, 142 Right), comparing MoCA-total and domain-specific scores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 35 publications
4
33
0
Order By: Relevance
“…In this study, it was found that patients with dominant hemispheric infarction exhibited poor performance with MoCA test. This finding agreed with Chan and colleagues (2017) [27] that hypothesized the poor performance of dominant hemisphere stroke patients on the MoCA most probably reflected the dependence of the MoCA constitutes on both receptive and expressive language skills as well as verbal working memory abilities, which are commonly involved following a dominant hemisphere stroke.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, it was found that patients with dominant hemispheric infarction exhibited poor performance with MoCA test. This finding agreed with Chan and colleagues (2017) [27] that hypothesized the poor performance of dominant hemisphere stroke patients on the MoCA most probably reflected the dependence of the MoCA constitutes on both receptive and expressive language skills as well as verbal working memory abilities, which are commonly involved following a dominant hemisphere stroke.…”
Section: Discussionsupporting
confidence: 92%
“…The MoCA has good psychometric properties and is a valid screening tool to detect post-stroke cognitive impairment [13]. Although a recent study [14] questioned the accuracy of the MoCA to assess attention and executive function by stroke lateralization, the majority of studies have shown the MoCA to be superior compared to other screening measures such as the MMSE [11, 15, 16]. While primarily considered a screening tool, the MoCA has been used as a cognitive outcome measure in longitudinal studies where lengthy neuropsychological testing is not often feasible.…”
Section: Assessmentmentioning
confidence: 99%
“…The choice of screening tool for cognition may also require consideration to ensure that the broad range of neuropsychological deficits that may arise post RH is assessed. The prior reported concern that some patients may present with domain specific cognitive impairments, which are overlooked in favour of a composite cognitive score, is reflected in findings within this thesis (Chan, 2017).…”
Section: Synthesismentioning
confidence: 78%
“…Chan and colleagues (2017) reported that the MoCA may under-estimate cognitive impairment in RH stroke. In their study the RH patient group, with intact cognition as assessed by the MoCA, showed impairments in information processing speed (57%), executive function (46%) and non-verbal memory (31%) on neuropsychological assessment (Chan, Altendorff, Healy, Werring, Cipolotti, 2017 (Blyth, Scott, Bond &, Paul, 2012). Research in the area of RH CCD suggests a disproportionate focus in referral processes and care-pathways on swallowing and motor speech deficits may exclude communications needs from provision of services.…”
Section: Introductionmentioning
confidence: 95%